prove that the statement 1/5+1/5^2+1/5^3 +...+1/5^n=1/4(1-1/5^n) is true for all positive integers n, write your proof in the space below

Hint:

(1-x^n) = (1-x)(1+x+x²+x³+...+xn-1)

To prove the statement 1/5 + 1/5^2 + 1/5^3 + ... + 1/5^n = 1/4(1 - 1/5^n) holds true for all positive integers n, we will use mathematical induction.

Step 1: Base Case
Let's verify the statement for the base case, where n = 1.

1/5 = 1/4(1 - 1/5^1)
1/5 = 1/4(1 - 1/5)
1/5 = 1/4(5/5 - 1/5)
1/5 = 1/4(4/5)
1/5 = 1/5

The base case holds true since both sides of the equation are equal.

Step 2: Inductive Hypothesis
Assume that the statement holds true for an arbitrary positive integer k, i.e.,

1/5 + 1/5^2 + 1/5^3 + ... + 1/5^k = 1/4(1 - 1/5^k).

Step 3: Inductive Step
Now, we need to prove that if the statement is true for k, then it is also true for k+1.

1/5 + 1/5^2 + 1/5^3 + ... + 1/5^k + 1/5^(k+1) = 1/4(1 - 1/5^(k+1))

From the inductive hypothesis, we know that:

1/5 + 1/5^2 + 1/5^3 + ... + 1/5^k = 1/4(1 - 1/5^k).

Substituting this into the equation, we have:

(1/4)(1 - 1/5^k) + 1/5^(k+1) = 1/4(1 - 1/5^(k+1))

Simplifying the left side of the equation:

(1 - 1/5^k)/4 + 1/5^(k+1) = (5^k - 1)/4 * (5^k * 5)/(5^k * 5^k * 4)

Multiplying both sides by 5^(k+1) * 4:

(5^k - 1) * 5 + 4 = (5^k * 5)

Multiplying:

5^(k+1) - 5 + 4 = 5^(k+1)

Simplifying:

5^(k+1) - 1 = 5^(k+1)

Both sides of the equation are equal, which completes the inductive step.

Step 4: Conclusion
The proof by mathematical induction shows that the statement 1/5 + 1/5^2 + 1/5^3 + ... + 1/5^n = 1/4(1 - 1/5^n) holds true for all positive integers n.